A Lack of Experience-Dependent Plasticity After More Than a Decade of Recovered Sight. (April 2015) - Huber, Elizabeth; Webster, Jason M.; Brewer, Alyssa A.; MacLeod, Donald I. A.; Wandell, Brian A.; Boynton, Geoffrey M.; Wade, Alex R.; Fine, Ione
In 2000, monocular vision was restored to M. M., who had been blind between the ages of 3 and 46 years. Tests carried out over 2 years following the surgery revealed impairments of 3-D form, object, and face processing and an absence of object- and face-selective blood-oxygen-level-dependent responses in ventral visual cortex. In the present research, we reexamined M. M. to test for experience-dependent recovery of visual function. Behaviorally, M. M. remains impaired in 3-D form, object, and face processing. Accordingly, we found little to no evidence of the category-selective organization within ventral visual cortex typically associated with face, body, scene, or object processing. We did observe remarkably normal object selectivity within lateral occipital cortex, consistent with M. M.'s previously reported shape-discrimination performance. Together, these findings provide little evidence for recovery of high-level visual function after more than a decade of visual experience in adulthood.